Comparative analysis of post crisis recovery in Southeast Asia. - Tan, Chuan Ghee. (2008)
This report focuses on the comparative analysis of post crisis recovery within three most affected countries, namely Thailand, Indonesia and Malaysia, whereby each with different economic and political fundamentals undertakes different reforms and responses to the crisis and presents different recovery trajectionaries.